MAIN APPROACHES TO THE DEVELOPMENT OF PROFESSIONAL PREPARATION OF STUDENTS OF TECHNICAL UNIVERSITIES - Muxtorova, Iroda; Kamoljon qizi, Muxtorova Iroda (IJBLE Scientific Publications Community Inc., 2020)
The purpose of this scientific article is to study the problem of developing students' competitiveness in the process of vocational education at a university from a scientific and pedagogical point of view and the development of basic approaches.